HEARING AS A WITNESS THE PERSON AGAINST WHOM CRIMINAL CHARGES MAY BE FILED - Mircea DAMASCHIN (Challenges of the Knowledge Society)
In the present study we address the issue of hearing as a witness, during the criminal trial, the person against whom, when considering the evidence included in the file, a charge could be pressed for a criminal offense. Referring to this issue, it is necessary to mention that the current Romanian Code of Criminal Procedure, entered into force on 2.1.2014, introduced a new article to the previous regulation which had enshrined the witness’s right against self incrimination. As we shall see, however, this new regulation does not apply to the present case. In these circumstances, the solution whereby the person against whom there are reasonable grounds for his/her participating in committing a criminal offense shall not testify as a witness arises from the case law of the European Court of Human Rights (hereinafter ECHR).